2014
DOI: 10.1016/j.freeradbiomed.2014.10.019
|View full text |Cite
|
Sign up to set email alerts
|

CROSSTALK BETWEEN Nrf2 AND NOTCH SIGNALING

Abstract: The transcription factor, Nrf2 (nuclear factor, erythroid derived 2, like 2) belongs to the CNC-bZip protein family, forming a transcriptosome with its direct heterodimer partner, sMaf, and co-factors such as CBP/p300. Nrf2 binds to one or more ARE (Antioxidant Response Element) that are located in the gene regulatory regions of the hundreds of Nrf2 target genes. The ARE is a key enhancer that is activated in response to endogenous or exogenous stresses in order to maintain cellular and tissue homeostasis. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…Recent literature suggests a cross talk between the NRF2 and Notch signaling pathways . We also showed that expression of both NICD1 and HES1 in oral squamous epithelial cells were regulated by NRF2, consistent with previous findings in hematopoietic stem cells, airway basal stem cells, and mouse embryonic fibroblasts .…”
Section: How Does Nrf2 Hyperactivation Contribute To Escc?supporting
confidence: 92%
“…Recent literature suggests a cross talk between the NRF2 and Notch signaling pathways . We also showed that expression of both NICD1 and HES1 in oral squamous epithelial cells were regulated by NRF2, consistent with previous findings in hematopoietic stem cells, airway basal stem cells, and mouse embryonic fibroblasts .…”
Section: How Does Nrf2 Hyperactivation Contribute To Escc?supporting
confidence: 92%
“…Nuclear factor (erythroid‐derived2)‐like 2 (Nrf2) is a transcription factor activated by ROS that regulates the expression of antioxidant proteins protecting against oxidative damage triggered by injury and inflammation. The interaction between Notch and Nfr2 is well known and appears to be crucial in many biological contexts as recently reviewed by Wakabayashi et al . In the endothelium it has been shown that Nfr2 can positively regulate the endothelial cells sprouting and vascularization by suppressing DII4/Notch4 pathway , thus suggesting that ROS can modulate Notch via Nfr2.…”
Section: Crosstalk Between Notch and Rosmentioning
confidence: 99%
“…In the downstream, ATF4 is found to be an interacting protein of Nrf2 , and Nrf2 is a positive regulator of ATF4 . Both Notch1 and HIF‐1α pathways can be regulated by Nrf2 .…”
Section: Crosstalk Between Keap1/nrf2 System and Other Cellular Signamentioning
confidence: 99%